Forecasting Regional Economic Growth in Aceh Using ARIMA Model: Evidence from Quarterly PDRB Data (2010–2025) - Muhamad Dupi; Muhammad Adil (Universitas Syiah Kuala, 2026)
The purpose of the study is to identify and predict regional economic growth in Aceh with a time series model which is the Autoregressive Integrated Moving Average (ARIMA) model. The analysis uses quarterly Gross Regional Domestic Product (GRDP) data (2010Q1-2025Q4), which is a result of official statistics. The values of the Augmented Dickey-Fuller test demonstrate that the series is not stationary at the level, but becomes stationary after the first difference, which means that the integration order is I(1). According to the BoxJenkins approach, the ARIMA(4,1,4) model is determined as the best possible specification, where the autoregressive term with lag 4 is highly statistically significant. Diagnostic tests are used to establish that the model meets stability and invertibility requirements whereby the residuals act as white noise. In terms of forecasting performance, the model demonstrates high accuracy, as indicated by low RMSE, MAE, and MAPE values, along with a Theil inequality coefficient close to zero. The forecasting results reveal a consistent upward trend in GRDP over the period 2025Q1 to 2030Q4, suggesting sustained economic growth in Aceh. These findings highlight the effectiveness of the ARIMA model as a reliable tool for short- to medium-term economic forecasting and provide valuable insights for regional policymakers in designing evidence-based development strategies.